Resistance to Antibacterials: Resistência aos Antibacterianos - Oliveira, Rita; Aires, Teresa (Gazeta Médica, 2018)
Antibacterial resistance is the acquire ability of bacteria to survive drug concentrations that inhibit or kill and is associated with excessive and inappropriate use of antibacterials. There are now bacteria unusually resistant to multiple types of antibacterials: the “superbugs”. If nothing will be done, by 2050 will die 10 million people worldwide, victims of infections by resistant bacteria.